1994
DOI: 10.1111/j.1464-410x.1994.tb16614.x
|View full text |Cite
|
Sign up to set email alerts
|

Artificial simulation of the early stages of renal stone formation

Abstract: A fixed solid surface, irrespective of its composition, in contact with normal urine sooner or later develops stone-forming compounds on its surface. The composition of these compounds depends on the supersaturated salts that are present. Under the experimental conditions citrate had only a limited capacity to inhibit COM crystal development. In contrast, phytic acid exhibited a much higher capacity for inhibition even at a considerably lower concentration than that of citric acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Morphological differences between wildtype and OPN KO mice appeared by the observation of polarized light optical microphotography and SEM, which showed that the crystals of OPN KO mice were small and uniform, with a sand‐like shape, and were different from those of WT mice, which were large and combined, many with a rosette‐shaped structure. These findings in OPN KO and WT mice have some resemblance to experimentally generated COM crystals in vitro ( (31)) and kidney stones of primary hyperoxaluria in humans, ( (32)) respectively. In WT mouse kidneys, the generated crystals contained OPN protein in immunohistochemical staining, which could be considered as matrix‐involving “stones.” These findings indicate that OPN is essential for the early phase of growth, fixation, and structural arrangement of calcium oxalate stones in mouse kidney.…”
Section: Discussionsupporting
confidence: 67%
“…Morphological differences between wildtype and OPN KO mice appeared by the observation of polarized light optical microphotography and SEM, which showed that the crystals of OPN KO mice were small and uniform, with a sand‐like shape, and were different from those of WT mice, which were large and combined, many with a rosette‐shaped structure. These findings in OPN KO and WT mice have some resemblance to experimentally generated COM crystals in vitro ( (31)) and kidney stones of primary hyperoxaluria in humans, ( (32)) respectively. In WT mouse kidneys, the generated crystals contained OPN protein in immunohistochemical staining, which could be considered as matrix‐involving “stones.” These findings indicate that OPN is essential for the early phase of growth, fixation, and structural arrangement of calcium oxalate stones in mouse kidney.…”
Section: Discussionsupporting
confidence: 67%
“…All these data seem to demonstrate that COD urolithiasis corre sponds to a more aggressive situation than COM urolith iasis, mainly due to hypercalciuria, but in both cases the participation of other factors not related to urine compo sition and consequently associated with the structure of the inner part of the kidney need to be considered. In fact, it must be taken into account that recent studies clearly demonstrate the important role of the antiadherent glycosaminoglycan layer that protects the inner walls of the kidney, preventing the development of incrustations that can act as nidus of calculi [6,7], consequently revealing the significance of a healthy uroepthelium for the pre vention of urolithiasis. Obviously, these latter factors must be related to the synthesis of glycoproteins and pro teoglycans and, therefore, a general genetic base of oxalocalcic urolithiasis would not be strange.…”
Section: Discussionmentioning
confidence: 99%
“…The animals were housed two per cage at 23t1uC and a relative Accepted for publication 14 Regularly (every 3±5 days) a 24-h urine sample was collected by housing the rats from each group in different metabolic cages. When the urinary level of InsP 6 reached a stable minimum value in the treated group, increasing amounts of InsP 6 were added to their liquid diet (61, 182 and 425 mg/L) until the urinary values became constant.…”
Section: Methodsmentioning
confidence: 99%